De Novo Genome Assembly of Limpet Bathyacmaea lactea (Gastropoda: Pectinodontidae): The First Reference Genome of a Deep-Sea Gastropod Endemic to Cold Seeps. (28th May 2020) - Liu, Ruoyu; Wang, Kun; Liu, Jun; Xu, Wenjie; Zhou, Yang; Zhu, Chenglong; Wu, Baosheng; Li, Yongxin; Wang, Wen; He, Shunping; Feng, Chenguang; Zhang, Haibin
Abstract: Cold seeps, characterized by the methane, hydrogen sulfide, and other hydrocarbon chemicals, foster one of the most widespread chemosynthetic ecosystems in deep sea that are densely populated by specialized benthos. However, scarce genomic resources severely limit our knowledge about the origin and adaptation of life in this unique ecosystem. Here, we present a genome of a deep-sea limpet Bathyacmaea lactea, a common species associated with the dominant mussel beds in cold seeps. We yielded 54.6 gigabases (Gb) of Nanopore reads and 77.9-Gb BGI-seq raw reads, respectively. Assembly harvested a 754.3-Mb genome for B. lactea, with 3, 720 contigs and a contig N50 of 1.57 Mb, covering 94.3% of metazoan Benchmarking Universal Single-Copy Orthologs. In total, 23, 574 protein-coding genes and 463.4 Mb of repetitive elements were identified. We analyzed the phylogenetic position, substitution rate, demographic history, and TE activity of B. lactea . We also identified 80 expanded gene families and 87 rapidly evolving Gene Ontology categories in the B. lactea genome. Many of these genes were associated with heterocyclic compound metabolism, membrane-bounded organelle, metal ion binding, and nitrogen and phosphorus metabolism. The high-quality assembly and in-depth characterization suggest the B. lactea genome will serve as an essential resource for understanding the origin and adaptation of life in the cold seeps.